Benefits, challenges, and recommendations of cultural instruction in second language learning (Journal of NELTA, 2024)
In the fast-growing globalized and culturally diverse society today, multiculturalism, i.e. knowledge of variegated culture, is considered to be an essential individual resource. This study examines the views of international postgraduate students on the benefits and challenges of incorporating cultural instruction into second language learning within an English-speaking higher education context in the UK. The objectives are to identify the advantages of cultural instruction, the barriers to its implementation in academic settings, and strategies to overcome these barriers. To achieve this, surveys and face-to-face discussions were conducted with a group of multiracial postgraduate language learners at Westminster University in London. The findings reveal that cultural instruction enhances learners’ understanding and engagement by providing contextually relevant information. The findings also show that there is a significant lack of institutional curricula and standards for integrating cultural materials into language learning, along with limited awareness among students and educators. The study recommends that academic stakeholders—including students, educators, and institutions—collaborate to incorporate cultural education into second language programs to enhance learning outcomes.